2017
DOI: 10.1093/cid/cix732
|View full text |Cite
|
Sign up to set email alerts
|

Innate, T-, and B-Cell Responses in Acute Human Zika Patients

Abstract: Understanding the immune response during acute Zika in humans will aid vaccine design and testing. In 5 acute patients, including 2 pregnant women, viral levels and innate, T-, and B-cell responses against Zika or dengue viruses are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
94
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(109 citation statements)
references
References 37 publications
13
94
1
1
Order By: Relevance
“…Immune cells were phenotyped by using flow cytometry at baseline and on Days 1, 2, 7, 14, 28, and 56 as previously described [23] using an LSRII cell analyzer (BD Biosciences, Franklin Lakes, NJ, USA) and FlowJo Software (TreeStar, Ashland, OR, USA). All samples were gated to exclude dead cells, debris, and doublets.…”
Section: Cellular Phenotypingmentioning
confidence: 99%
“…Immune cells were phenotyped by using flow cytometry at baseline and on Days 1, 2, 7, 14, 28, and 56 as previously described [23] using an LSRII cell analyzer (BD Biosciences, Franklin Lakes, NJ, USA) and FlowJo Software (TreeStar, Ashland, OR, USA). All samples were gated to exclude dead cells, debris, and doublets.…”
Section: Cellular Phenotypingmentioning
confidence: 99%
“…In humans, virus‐specific antibodies are seen to develop as early as 3 days after the onset of fever, although in some studies IgM was not detectable until 8 days after symptom onset with IgG developing even later in flavivirus‐naive patients . Cross‐reactivity between ZIKV and antibodies to dengue virus has been observed, complicating both ZIKV diagnosis and assessment of vaccine‐induced immunity .…”
Section: Modeling Immune Control Of Viremiamentioning
confidence: 99%
“…Previously Lai. et al confirmed that the early expansion of the antibody-secreting B cells secrets ZIKV-specific immunoglobulins G, A but also M (45). Moreover, germinal centers (GC) are responsible for generating long-lived, high-affinity Antibody Secreting Cells (ASC) that in turn are able to generate a better-quality response against re-infections (46).…”
Section: Discussionmentioning
confidence: 93%